Rilpivirine Plasma and Cervicovaginal Concentrations in Women During Pregnancy and Postpartum. (1st July 2018) - Eke, Ahizechukwu C.; Chakhtoura, Nahida; Kashuba, Angela; Best, Brookie M.; Sykes, Craig; Wang, Jiajia; Stek, Alice M.; Smith, Elizabeth; Calabrese, Samantha; Capparelli, Edmund V.; Mirochnick, Mark
Abstract : Background: Concentrations of antiretrovirals in the genital tract play a key role in preexposure prophylaxis. This study aims to describe rilpivirine (Edurant) concentrations in the genital tract in pregnant and postpartum women. Methods: International Maternal Pediatric Adolescent AIDS Clinical Trials Protocol P1026s is an ongoing, prospective study of antiretroviral pharmacokinetics in HIV-infected pregnant women that include a cohort receiving rilpivirine combination regimen. Intensive pharmacokinetics evaluations were performed at steady state during the second and third trimester, and postpartum. Plasma and directly aspirated cervicovaginal fluid (CVF) samples were collected at 4 time points around an observed dose and measured using high-performance liquid chromatography with ultraviolet detection, [plasma; lower limit of quantification (LLQ) = 10 ng/mL] or liquid chromatography-tandem mass spectrometry (CVF; LLQ = 1 ng/mL). Results: A total of 24 women were included in the analysis. For all time points combined, median (interquartile range) rilpivirine concentrations were 70 ng/mL (23–121) in CVF and 92 ng/mL (49–147) in plasma. The CVF to plasma AUC(0–4) ratios were significantly higher in the second (0.90, 90% CI: 0.61 to 1.46) and third trimesters of pregnancy compared with postpartum (0.40, 90% CI: 0.19 to 0.87). Three of 189 (1.6%) plasma samples in 2 women were below the LLQ and the corresponding CVF concentrations. Seventeen additional CVF concentrations (10.6%) were below LLQ in 13 participants. No major safety concerns were noted. Conclusions: Rilpivirine concentrations were higher in the CVF during pregnancy compared with postpartum. CVF Rilpivirine is likely to achieve inhibitory concentrations effective for preventing peripartum HIV transmission.